Step-by-step explanation:
(3X-20)+(3X+5)=111(( SINCE 111 IS TOTAL ANGLE
6X-15=111
6X=126
X=21
EFG=3×21-20
=63-20=43
Answer:
12¾
Step-by-step explanation:
x - ¾ = 12
x = 12 + ¾
c = 12¾ or 12.75
<span>
You can write the equation in point-slope form, which has the format <em>y-y</em>subscript1=<em>m</em>(<em>x-x</em>subscript1), with <em>y</em>subscript1 and <em>x</em>subscript1 being the y and x coordinates for a point on the line, and <em>m</em> being the slope. </span>
<span /><span>Substitute a y and x coordinate into the equation so you have <em>y</em>-6=<em>m</em>(<em>x</em>-2)</span>
<span /><span><span>Then find the slope so you can replace <em>m</em>. The slope formula is <em />(<em>y</em>subscript2-<em>y</em>subscript1)/(<em>x</em>subscript2-<em>x</em>subscript1). </span><span>Substitute the coordinates in so you have <em>m</em>=(16-6)/(4-2), which simplifies to 10/2 and then 5.</span></span>
<span><span /></span><span>Now the equation is <em>y</em>-6=5(<em>x</em>-2)</span>
<span />If you want a different form, for example slope-intercept form, you can change it to that:
<span><em>y</em>-6=5(<em>x</em>-2)</span>
<span><em>y</em>=5x-4</span>
<u><em></em></u>
Answer:

Step-by-step explanation:
<u><em>STEP:-1</em></u>
Given that events A and B are independent then
P(A ∩B ) = P(A) P(B)
Given that P(A) = 2/5 and P(B) = 1/5
<u><em>STEP:- 2</em></u>
P(A ∩B ) = P(A) P(B)


<u><em>Step(iii):-</em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em /></u>
<u><em /></u>